Malaysia my second home: The influence of push and pull motivations on satisfaction. (August 2017) - Wong, Brian Kee Mun; Musa, Ghazali; Taha, Azni Zarina
Abstract: Malaysia's second home retirement tourism programme attracted participants globally and reached its peak in 2013. The numbers started to dwindle in 2014, particularly among the once-top nationalities: the British, Japanese, and Iranians. The lack of data on the participants' motives and satisfaction levels in quantitative forms justifies the need for this study. This research examines the 'Malaysia My Second Home' (MM2H) participants' motivation, satisfaction, and the relationship between the two constructs. Of the 504 usable samples, we used 280 for scale development and 224 for the structural model assessment. The empirical analyses validated the conceptual model. The results revealed four 'push' and seven 'pull' motivation factors respectively. Push motivations (β = 0.568) displayed a stronger influence on the participants' overall satisfaction. The findings suggest the need for human centric marketing strategies and improvement in the central government management to enhance the attractiveness of the MM2H programme for international retirees. Highlights: This study examines the causal relationship between motivation and satisfaction among Malaysia My Second Home participants. We use mixed-method in developing the instrument measures to study the constructs quantitatively. Out of 504 usable samples, we use 280 for scale development and 224 for structural model assessment. Our results reveal four push motivations and seven pull motivations. Push motivations influence more the participants' overall satisfaction, particularly 'unfavourable political' and 'security' and 'escapism'.